Reputation as Capital (Global Journal of Management and Business Research, 2023)
Abstract- Decentralized Autonomous Organizations DAOs have the potential to upgrade finance This paper evaluates the design of and system requirements for a decentralized cryptocurrency venture capital investment club that is operating as a DAO DAOIC The design of the proposed DAOIC enables investors to substitute capital commitments by way of reputation token staking on proposed portfolio companies The proposed design has the potential to lower capital requirements and free up liquidity for decentralized smart contract coordinated investment vehicles
Keywords: decentralized autonomous organization; venture capital; reputation; non-fungible tokens; fungible tokens